Pengaruh Pendekatan CPA (Concrete, Pictorial, Abstract) Terhadap Pemahaman Konsep Matematika Siswa Kelas 2 SD Pamulihan 01 - Arlinka, Silvana Madya (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the CPA (Concrete, Pictorial, Abstract) approach on the mathematical concept understanding of students in grade 2 at Pamulihan 01 Primary School. The background of this study stems from the finding that the learning methods used by teachers are not in line with the cognitive development stages of children, resulting in the students' mathematical concept understanding not developing optimally. This study used a pre-experimental method with a One Group Pretest-Posttest design and involved 25 students as subjects. Data were collected through implementation observation sheets, student observation sheets, and pretest and posttest tests. Data analysis was conducted quantitatively. The results showed that the average posttest score (71.04) was higher than the pretest score (63.42). Hypothesis testing using the Paired Sample t-Test through SPSS version 16 at a significance level of 5% produced a sig. value of 0.014, which is smaller than 0.05. These findings indicate that the CPA approach has a significant effect on improving students' understanding of mathematical concepts, so H0 is rejected and Ha is accepted.